The Psychometric Properties of the Environmental Worry Index - Oguntayo, Rotimi; Gutierrez Vega, Marisela; Esparza Del Villar, Oscar Armando (2024)
Introduction: Environmental-related hazards are a global problem; consequently, an Environmental Worry Index (EWI) was developed; however, the psychometric properties of this scale in the Spanish population are unavailable. Purpose: The objective of this study was to adapt and examine the psychometric properties of an Environmental Worry Inventory (EWI) in a Spanish-speaking student population. Methodology: This study adopted a cross-sectional design. It used a snowball sampling technique to collect data using the compact questionnaire comprise of EWI, Climate Anxiety Scale (CAS), and Big Five Inventory (BFI-15) from 251 participants in 2023 among students of Autonomous University of Ciudad Juarez (UACJ), Juarez, Mexico. Results: Results of exploratory factor analysis (EFA), the Kaiser-Meyer-Olkin (KMO=0.891) and Bartlett's Test of Sphericity (p < 0.001) showed adequate data. Confirmatory factor analysis (CFA; χ2 (5) = 78,595, CFI = 0.94, and RMSEA=0.078) demonstrated adequate goodness of fit. EWI was associated with CAS, and neuroticism dimension of BFI-15. It has an acceptable overall Cronbach Alpha coefficient (α = 0.890); the two subscale factors’ reliability coefficients ranged from .80 to .89. Conclusion: The study concluded that EWI is reliable, valid and recommended for use among Mexicans especially the Spanish speaking students.